2017
DOI: 10.5194/acp-17-6517-2017
|View full text |Cite
|
Sign up to set email alerts
|

Summer ozone in the northern Front Range metropolitan area: weekend–weekday effects, temperature dependences, and the impact of drought

Abstract: Abstract. Contrary to most regions in the US, ozone in the northern Front Range metropolitan area (NFRMA) of Colorado was either stagnant or increasing between 2000 and 2015, despite substantial reductions in NO x emissions. We used available long-term ozone and NO x data in the NFRMA to investigate these trends. Ozone increased from weekdays to weekends for a number of sites in the NFRMA with weekend reductions in NO 2 at two sites in downtown Denver, indicating that the region was in a NO x -saturated ozone … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 44 publications
(72 reference statements)
3
30
0
Order By: Relevance
“…Conversely, it appears that local O 3 production has increased under declining NO x . Similar conclusions were derived from a recent analysis of trends in weekday/weekend differences in O 3 and NO x at selected NCFR sites by Abeleira and Farmer (2017). Their study found that "most sites in the NFRMA were NO x -saturated, but are transitioning to, and in one case may already have reached, the peak P(O 3 ) cross-over point between NO x -saturated and NO x -limited regimes".…”
Section: Ozone At Welbysupporting
confidence: 78%
“…Conversely, it appears that local O 3 production has increased under declining NO x . Similar conclusions were derived from a recent analysis of trends in weekday/weekend differences in O 3 and NO x at selected NCFR sites by Abeleira and Farmer (2017). Their study found that "most sites in the NFRMA were NO x -saturated, but are transitioning to, and in one case may already have reached, the peak P(O 3 ) cross-over point between NO x -saturated and NO x -limited regimes".…”
Section: Ozone At Welbysupporting
confidence: 78%
“…Its concentration begins to increase gradually from January and demonstrates a downward trend after reaching a maximum in June (79.6 ± 22.8 µg/m 3 in 2014) or August (96.3 ± 18.1 µg/m 3 in 2015), and the minimum of the whole year is in November (30.0 ± 9.7 µg/m 3 in 2014) or December (28.2 ± 5.9 µg/m 3 in 2015). Temperature directly influences O 3 production by interfering with the photochemical reaction speed and the volatile organic compounds (VOCs) emissions [40,41]. The local emissions of precursors (NO x , VOC, and CO) also have an important effect on the regulation of O 3 variability.…”
Section: Diurnal Variationsmentioning
confidence: 99%
“…O 3 has a temperature-dependent chemistry (Pusede et al, 2015), and temperature was used in some studies as a surrogate to indicate O 3 formation via the O 3 -temperature association, both at individual measuring sites and on a greater regional scale (Oikonomakis et al, 2018). The O 3 -temperature relationship originates in: (1) temperaturedependent biogenic VOC emissions, (2) thermal decomposition of PAN to HO x and NO x , (3) increased likelihood of favorable meteorological conditions for ozone formation (Abeleira and Farmer, 2017). However, there are major uncertainties in the mechanisms underlying the temperature-dependent changes in O 3 concentrations, their interactions, and relative contributions in rural and remote regions (Romer et al, 2018).…”
Section: Complex Atmospheric Chemistry Of Omentioning
confidence: 99%
“…However, there are major uncertainties in the mechanisms underlying the temperature-dependent changes in O 3 concentrations, their interactions, and relative contributions in rural and remote regions (Romer et al, 2018). Ozone chemistry regimes are shifting as precursor emissions are changing (Abeleira and Farmer, 2017). Moreover, meteorology-dependent O 3 chemistry implicates the impact of ongoing climate change on O 3 .…”
Section: Complex Atmospheric Chemistry Of Omentioning
confidence: 99%
See 1 more Smart Citation